Binarization for eliminating calibration in fiberscope image processing - Minkyung, Kim; Yeo, Y.-S.; Shin, H.-J. (Elsevier BV, 2021)
High-density coherent fiber bundles, mainly used for high-resolution fiberscopes, consist of non-circular cores and have various optical noises such as auto-fluorescence, crosstalk, and honeycomb artifacts that may require excessive image processing. Binarization was applied to post-image processing to eliminate a calibration used as pre-image processing for traditional fiberscope image reconstruction. It was able to significantly reduce the complexity of implementing core peak detection and effectively reduce the overall processing time. For binarization, the global thresholding suggested by Otsu and the local thresholdings suggested by Bernsen, Niblack, and White and Rohrer were used. By applying a dynamic method to our method, we can further simplify the process and apply it to image sequencing. When evaluating the results comprehensively, the local thresholding proposed by Bernsen was best suited for interpolating our fiberscope images. By introducing binarization combined with local thresholding in post-image processing, we were able to successfully eliminate the preliminary calibration process and reduce the burden of overall image processing for image reconstruction in a high-resolution fiberscope. ？ 2021 The Author(s)